Studi Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kepuasan Karyawan: Survey Pada Manajemen Tingkat Menengah PT KMK Global Sports - , Catur Marhaendra ([Yogyakarta] : Universitas Gadjah Mada, 2012)
High dependency of workers for Labor Intensive Industry and more competitive Labor Intensive Industry at National , regional and International level are triggers of high turn over rate in the Industry, not only low level workers or Middle Management. High turn over rate in the Industry creates unstability of operations and in a long run creates competitive disadvantage of the Industry at all scale, national, regional and International.. In this thesis, Hypotesis of correlation of Motivation and Working Environment to Employee Satisfaction were studied in one of Labor Intensive Manufacturer. High rate of Employee satisfaction is a key factor to retain workers while Motivation and good working environment are key variables for Employee satisfaction. Result of study through Primer data processing with questionaire method from some samples obviuously explains that significant relation occurs between motivation and good working environment to Employee Satisfaction. Correlation also occurs separately between Motivation and Employee Satisfaction and Good working environment and Employee satisfaction